Guidelines for Cultural Management as Part of Participation of Cultural Networks and Communities - Upanisakorn, Wipaphan; Khayantam, Raschai (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
This academic article aims to present the concept of community involvement. Network, culture and community concept factors affecting cultural engagement and management. With mentioning factors in enhancing Conservation of arts, culture, traditions and local wisdom, engage the community in participation and management. This may involve the nature of collaboration on one or more of the subjects, to achieve the goals that were set. He change or development will take place with cooperation from the main institutions in the community, such as temples, houses and schools, which are members of the community for sustainable development.